The Temporal Dynamics of Cognitive Processing - John Magnotti (Frontiers Research Topics, 2016)
From our ability to attend to many stimuli occurring in rapid succession to the transformation of memories during a night of sleep, cognition occurs over widely varying time scales spanning milliseconds to days and beyond. Cognitive processing is often influenced by several behavioral variables as well as nonlinear interactions between multiple neural systems. This frequently produces unpredictable patterns of behavior and makes understanding the underlying temporal factors influencing cognition a fruitful area of hypothesis development and scientific inquiry. Across two reviews, a perspective, and twelve original research articles covering the domains of learning, memory, attention, cognitive control, and social decision making this research topic sheds new light on the temporal dynamics of cognitive processing.